Gynecologic health of women with multiple sclerosis: An overview on the current status and findings of Pap tests in a low-income setting - Masoud Etemadifar; Shima Shoeib; Mehri Salari; Mohammadreza Etemadifar; Nahad Sedaghat (PLoS ONE, 2025)
Background Women with MS (wwMS), particularly ones in low-income settings, and exposed to disease-modifying therapy (DMT), could have specific gynecological health-related issues. Aim To assist policy making and lead further research by describing the current status of gynecological health and Pap test results in wwMS. Methods Cross-sectional study on wwMS living in Isfahan, Iran. Participants were surveyed and referred for a Pap test, results of which were compared with 1:2 age- and socioeconomic status-matched healthy controls (HC). Primary outcome was the degree of non-benign squamous/glandular cell abnormalities. Secondary outcomes were presence of evidence of infection, and the degree of benign inflammatory/reactive changes. Logistic regression models were utilized for analyses. Results 197 wwMS were included (mean age [SD], 41.2 [8.3]; median EDSS (IQR) 1.5 [0.5]). 74.1% reported having sexual activity more than once per week in the past year. For contraception, 21.6% and 16.8% used calendar-based methods and male condoms, respectively. 7% had contracted a gynecological infection in the past. Only 1% had received HPV vaccination. Compared to HC, benign reactive/inflammatory changes in Pap tests were less frequently seen in the wwMS (OR: 0.3; 95% CI: 0.2, 0.4; p <  0.001), while evidence of infection was seen more frequently (OR: 11.5, 95% CI: 3.3, 40; p <  0.001). Results were consistent across DMT groups except anti-CD20 therapies. Additionally, the frequency of non-benign changes in wwMS was two times of that in the HC, but the study lacked adequate power to confirm statistical significance (1.5% vs. 0.8%, OR: 2; 95% CI: 0.4, 10.1; p =  0.39). Conclusion There is room for improvement of the gynecological health status of wwMS who live in low-income settings. Also, findings support an immune dysfunction in the cervices of DMT-exposed wwMS. Additionally, further research is merited to determine the risk of changes of malignant potential in cervices of wwMS.